Managing Change Through Leadership Discourse: An Experience in the Surgical Ward - Ahmad, Hafiz Naweed; Malik, Wusqa Sultana; Malik, Fakiha Sultana (Biological and Clinical Sciences Research Journal, 2025)
Effective leadership is crucial in managing change within healthcare organizations. While leadership is often associated with formal roles, individuals without designated authority can still influence meaningful transformation through visionary approaches. This case study describes the implementation of a change initiative in a surgical ward using transformational leadership and soft systems methodology (SSM), focusing on the improvement of the process for handling patient investigation samples. Objective: To transform the disorganized process of sending patient samples from the surgical ward to the pathology laboratory, thereby enhancing patient care, improving workflow, and promoting a learning-friendly environment. Methods: A mixed-methods approach was adopted. The initiative was led by a senior registrar without a formal administrative role, using transformational leadership principles and the Soft Systems Methodology. Stakeholders including postgraduate trainees, house officers, and nurses were engaged through meetings, focus groups, and structured interviews. Quantitative data were collected using four core questions, while qualitative themes were derived from focus group discussions. Change resistance and support were assessed using SWOT and force field analyses. Results: All stakeholder groups unanimously recognized the need for change. A majority supported the new process and its implementation method, although concerns were raised regarding staff limitations and resistance from some junior personnel. Feedback revealed that improved organization, reduced patient burden, and enhanced team coordination were key outcomes. The intervention was successfully implemented and anchored in ward culture through leadership influence, motivation, and departmental collaboration. Conclusion: This case study highlights that meaningful change in healthcare can be achieved through informal leadership, ethical motivation, and inclusive stakeholder engagement. Applying transformational leadership and SSM facilitated the successful redesign of a long-standing flawed process, even in a resource-constrained environment. Continuous motivation, feedback, and adaptive strategies were essential for sustaining the change.